Protocol to screen chemicals to enhance homology-directed repair in CRISPR-Cas9 gene editing - Min Ju Jo; Hye Jin Nam (STAR Protocols)
Summary: CRISPR-Cas9-based gene editing via homology-directed repair (HDR) enables precise modifications, though its efficiency is limited by the prevalence of non-homologous end joining (NHEJ). Here, we present a protocol for enhancing HDR efficiency by identifying chemicals using high-throughput screening (HTS). We describe steps for designing 96-well plates, executing HTS, and performing data analysis. We then detail procedures for identifying small molecules that improve HDR-associated gene editing. This protocol has potential application in HTS analysis focused on discovering reliable HDR enhancers.For complete details on the use and execution of this protocol, please refer to Jang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.